2016
DOI: 10.3390/f7070151
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of Climate Change Effects on Dominant Height of Larch Plantations in Northern and Northeastern China

Abstract: Abstract:Determining the response of dominant height growth to climate change is important for understanding adaption strategies. Based on 550 permanent plots from a national forest inventory and climate data across seven provinces and three climate zones, we developed a climate-sensitive dominant height growth model under a mixed-effects model framework. The mean temperature of the wettest quarter and precipitation of the wettest month were found to be statistically significant explanatory variables that mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(62 reference statements)
2
2
0
Order By: Relevance
“…Our study found that climate was the main factor affecting the productivity of larch in the study area. The results were highly consistent with other studies ( Zang et al., 2016 ; Duan et al., 2022 ). The climatic factors affecting the site index of larch were mainly the temperature of the warmest quarter (BIO10), the mean diurnal range (BIO2), and the annual precipitation (BIO12) ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found that climate was the main factor affecting the productivity of larch in the study area. The results were highly consistent with other studies ( Zang et al., 2016 ; Duan et al., 2022 ). The climatic factors affecting the site index of larch were mainly the temperature of the warmest quarter (BIO10), the mean diurnal range (BIO2), and the annual precipitation (BIO12) ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…Area proportions of the distribution regions with different larch SI values for current and future periods (2030s, 2050s, and 2090s) under SSP1-2.6, SSP2-4.5, and SSP5-8 climate scenarios. consistent with other studies (Zang et al, 2016;Duan et al, 2022). The climatic factors affecting the site index of larch were mainly the temperature of the warmest quarter (BIO10), the mean diurnal range (BIO2), and the annual precipitation (BIO12) (Figure 3).…”
Section: Figuresupporting
confidence: 91%
“…Besides these aforementioned factors, climate factors such as temperature, light and precipitation are not negligible in determining tree growth [10]. Climate-sensitive tree growth models have also been developed recently [11][12][13]. The climate, site condition and competition interactively influence individual tree growth.…”
Section: Introductionmentioning
confidence: 99%
“…Dominant tree height, for example, has been used to calculate the site index for even-aged and pure forests [ 6 ]. The dominant height growth model with climate factors is used to help predict the site index under future climate change and to analyze the adaptation strategies of trees [ 7 ].…”
Section: Introductionmentioning
confidence: 99%